Effects of MHD free convection and mass transfer on the flow past a vibrating infinite vertical circular cylinder - Agrawal A.K.; Kishor B.; Raptis A. (My University, 2025)
The effects of MHD free convection and mass transfer are taken into account on the flow past a vibrating infinite isothermal and constant heat flux vertical circular cylinder. The expressions for velocity, temperature, concentration and skin-friction of the fluid are obtained in closed form by using Laplace transform technique. The effects of Pr (Prandtl number), Sc (Schmidt number), Gr (Grashof number, Gr>0 implies cooling and Gr<0 heating of the cylinder), Gm (modified Grashof number), M (magnetic field parameter) and variation of time on velocity distribution have been studied graphically. The results presented in this paper agree with the results of Lien and Chen when magnetic parameter approaches zero. © 1989 Springer-Verlag.